Communicative Task and Competence: Reflections on a Focus Group - Vallejo Gómez, Mercedes; Martínez Marín, Juan Diego (Íkala, Revista de Lenguaje y Cultura, 2011)
The objective of this article is to describe a foreign language learning management proposal erected from the identification and organization of a communicative task that functions as an articulating element in the communicative competence development. This research proposal was conducted under the action research bases and under the support of participant-teachers within the intention of creating a collaborative work supported on the reflection, critical dialogue and transformation (Burns, 1999). A teachers' focus group was set, journals were made, a diagnostic survey was conducted as well as some semi-structured interviews to teachers; and a learning and teaching management guide was built collaboratively. As a result, we obtained the construction of a guidance document, as one of the partial findings of this ongoing research, that takes into account the communicative competence as a part of an integral concept of language that conveys social agents into specific situations of intercultural communication and that takes into account the following: the definition of a communicative task; the pre-tasks planning leading to the achievement of the communicative task; the task assessment through formative strategies; the activation of learning strategies; the development of some tasks in physical and virtual environments; and the teacher's reflections once the cycle has been completed. The re-validation of the activities suggested by teachers in the foreign language learning process constitutes itself into integrating factor for the development of a communicative task which has inputs and outputs materialized in a series of different instruments concerning comprehensive, interactive and productive conditions.